2008
DOI: 10.1007/s12098-008-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive smoking on lung function and respiratory infection

Abstract: Passive smoking has an unfavorable effect in respiratory function of children and predisposes them to respiratory tract infections. Every effort should be undertaken in order to avoid exposure of children to environmental tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
1
5
0
3
Order By: Relevance
“…Our prevalence of SHS exposure at home in children aged 6 years and younger was comparable to another Dutch study, which reported a prevalence of 10% for a slightly younger age group (0-4 years) in 2009 [18]. Our findings on SHS exposure deviate from the compelling evidence on the relationship between SHS and respiratory complaints [3,4,[19][20][21][22][23][24], asthma and wheezing [4,23,24], and respiratory tract infections [5,19,[25][26][27] in children. The lack of association in our study is most likely due to methodological issues such as the cross-sectional design of the study, the moderate participation rate, possible parental underreporting of their smoking behaviour and selective participation.…”
Section: Main Findingssupporting
confidence: 63%
See 1 more Smart Citation
“…Our prevalence of SHS exposure at home in children aged 6 years and younger was comparable to another Dutch study, which reported a prevalence of 10% for a slightly younger age group (0-4 years) in 2009 [18]. Our findings on SHS exposure deviate from the compelling evidence on the relationship between SHS and respiratory complaints [3,4,[19][20][21][22][23][24], asthma and wheezing [4,23,24], and respiratory tract infections [5,19,[25][26][27] in children. The lack of association in our study is most likely due to methodological issues such as the cross-sectional design of the study, the moderate participation rate, possible parental underreporting of their smoking behaviour and selective participation.…”
Section: Main Findingssupporting
confidence: 63%
“…Maternal smoking during pregnancy has been associated with an increased risk of recurrent wheezing and asthma during the first years of life [3], and even reduction in lung function [4]. Furthermore, ETS exposure has been associated with an increased risk of childhood upper and lower respiratory tract infections compared to children without ETS exposure [5]. Limited studies have evaluated the effects of ETS exposure in children with a genetic predisposition for asthma [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…German and his colleagues also indicated that they did not find an association between smoking and symptomatic respiratory infection in a cohort of military recruits in Greece [48]. In addition, previous studies performed in children provide some supports for an impact, such that children who were exposed to environmental tobacco smoke had higher risk for URTI than children who lived in a smoke-free environment [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Utvrdili su da deca izložena duvanskom dimu imaju veći rizik da obole od infekcija donjih disajnih puteva. Izmerene vrednosti plućnih prametara su kod njih bile visoko značajno smanjene u odnosu na decu koja nisu bila izložena duvanskom dimu (p< 0,001) [20].…”
Section: Diskusijaunclassified